Consensus on the use of oral isotretinoin in dermatology - Brazilian Society of Dermatology, - Ediléia Bagatin; Caroline Sousa Costa; Marco Alexandre Dias da Rocha; Fabíola Rosa Picosse; Cristhine Souza Leão Kamamoto; Rodrigo Pirmez; Mayra Ianhez; Hélio Amante Miot (Sociedade Brasileira de Dermatologia, 2021)
Abstract Background: Isotretinoin is a synthetic retinoid, derived from vitamin A, with multiple mechanisms of action and highly effective in the treatment of acne, despite common adverse events, manageable and dose-dependent. Dose-independent teratogenicity is the most serious. Therefore, off-label prescriptions require strict criteria. Objective: To communicate the experience and recommendation of Brazilian dermatologists on oral use of the drug in dermatology. Methods: Eight experts from five universities were appointed by the Brazilian Society of Dermatology to develop a consensus on indications for this drug. Through the adapted DELPHI methodology, relevant elements were listed and an extensive analysis of the literature was carried out. The consensus was defined with the approval of at least 70% of the experts. Results: With 100% approval from the authors, there was no doubt about the efficacy of oral isotretinoin in the treatment of acne, including as an adjunct in the correction of scars. Common and manageable common adverse events are mucocutaneous in nature. Others, such as growth retardation, abnormal healing, depression, and inflammatory bowel disease have been thoroughly investigated, and there is no evidence of a causal association; they are rare, individual, and should not contraindicate the use of the drug. Regarding unapproved indications, it may represent an option in cases of refractory rosacea, severe seborrheic dermatitis, stabilization of field cancerization with advanced photoaging and, although incipient, frontal fibrosing alopecia. For keratinization disorders, acitretin performs better. In the opinion of the authors, indications for purely esthetic purposes or oil control are not recommended, particularly for women of childbearing age. Conclusions: Approved and non-approved indications, efficacy and adverse effects of oral isotretinoin in dermatology were presented and critically evaluated.